(untitled) (Bioscience Journal, 2016)
Tropidurus comprises a Neotropical genus of lizard that currently has about 30 species widely distributed in the South American. Among these species, Tropidurus torquatus, which has the characteristic of great physiological plasticity, occupying a variety of habitats in open areas and urbanized environments. Considering this, the aim of the study was to investigate the germinative cells and spermatogenesis of a population of T. torquatus in an urban area under Cerrado Biome influences to understand how to establish the temporal development of germinative cells and spermatogenesis during a period of one year. Individuals were obtained in the Zoological Collection of Vertebrates at the Universidade Federal de Mato Grosso (UFMT), and the germinative cells and full spermatogenesis were described with light microscopy. Tropidurus torquatus presented germ cells with similar characteristics already documented for the other species of lizards and reptiles. Spermatogonia type A and B, primary and secondary spermatocytes, and spermatids were present in almost all months evaluated. The gonadosomatic ratio presented its highest value in October, moment in which spermatogenesis presented all the germinative cells and spermatozoa in the lumen, of the seminiferous tubules. In the seasonal climate of the Cerrado Biome, we observe discontinuous spermatogenesis in T. torquatus with the production of spermatozoa in almost every month of the year, however with sperm storage in the epididymis during the phase of testicular regression.